Experimental Study of Optimizing Forming Grinding Teeth Process based on Six Sigma Test Design - Lijun Liu; Yudan Zhang; Zhipeng Chang (Jixie chuandong)
In order to determine the significant characteristic factors affecting grinding burn， according to the actual conditions， the DOE（Design of Experimentation）of Six Sigma Quality Tool is used to carry out experiments， and the significant characteristic factors affecting grinding burn are researched， and the optimum grinding process parameters are fitted. The results show that， the optimal grinding parameters are obtained through simulation of rough grinding and fine grinding， and the experimental processing is carried out， and the grinding burn rate of the formed grinding teeth is effectively controlled， which provides a basis for improving efficient and reducing production cost of enterprises.